2020
DOI: 10.37934/cfdl.12.3.110
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effect of Different Turbulence Models on The CFD Predictions of NACA0018 Airfoil Aerodynamics

Abstract: The analysis of aerodynamic forces on two-dimensional airfoils and flow phenomena associated with different Reynolds number has been widely investigated for aerospace vehicles and wind turbines. Various numerical methods have been used with different turbulence models, and the discrepancy in flow physics differs between each model. This work presents the numerical analysis of the aerodynamic performance of NACA 0018 airfoil using different turbulence models. The Computational Fluid Dynamics (CFD) solver, Ansys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…To close the system (1) and to determine the coefficient of turbulent viscosity. The different turbulence models were discussed in a study by Khan et al, [18]. The Spalart-Allmaras model was used herein, which was well-proven at the analysis of problems of external flow around bodies and is described in detail in the study by Spalart and Allmaras [19].…”
Section: Methodology 21 Mathematical Statement Of the Problemmentioning
confidence: 99%
“…To close the system (1) and to determine the coefficient of turbulent viscosity. The different turbulence models were discussed in a study by Khan et al, [18]. The Spalart-Allmaras model was used herein, which was well-proven at the analysis of problems of external flow around bodies and is described in detail in the study by Spalart and Allmaras [19].…”
Section: Methodology 21 Mathematical Statement Of the Problemmentioning
confidence: 99%
“…A more promising approach is to include a transition model to more accurately simulate the complex boundary layers typical for airfoils and high-lift configurations. Khan et al [27] successfully used the k-k L -ω model to improve the predictive accuracy for a symmetrical airfoil. This was also tested for slat and airfoil configurations investigated in this paper, but resulted in a drastic over-prediction of the maximum lift (see Figure 6).…”
Section: Turbulence Modelmentioning
confidence: 99%
“…Eleni et al, [25] demonstrated that the kῳ-SST model is appropriate for NACA 0012 airfoil design and provides accurate analyses and vortex at all angles of attack. Furthermore, according to references [28,30,31], k SST simulated the boundary layers along the airfoil's wall, which is necessary for capturing accurate results through numerical computations. Based on these researches, the Kῳ-SST model is selected for all domains in the current work for both airfoils with and without inclined trailing edge.…”
Section: Numerical Simulationmentioning
confidence: 99%